Chemical weed control in winter wheat: Efficiency and economic return - Uoti, Juhani; Juvankoski, Tuomo (Agricultural and Food Science, 1979)
In field trials in Vihti during the years 1968—1978 the average yield increase in winter wheat obtained with chemical Weed control was 439 kg/ha with a yield level of 3 704 kg/ha. The moisture content in percentages was 1.2 % lower in the sprayed plots than in the unsprayed plots. The number and the dry weight of weeds was greatly reduced by the spraying. The producer price for the wheat being at present 1 mk/kg, the value of the yield increase for the farmer is 439 mk/ha, whereas the decrease of the moisture content saves in drying costs 36 mk/ha. When the spraying costs estimated at 153 mk/ha have been deducted from these figures, the net return for the farmer is 322 mk/ha.